Deep Learning sebagai Pendukung dalam Pembelajaran Bermakna untuk Siswa Sekolah Dasar di Era Merdeka Belajar - Lia Yulia (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
The digital transformation of the 21st century encourages the education sector to continuously adapt through the use of technology in order to create more effective and meaningful learning. The Kurikulum Merdeka provides space for learning innovations that are student-centered while strengthening higher-order thinking skills and the values of the Profil Pelajar Pancasila. Deep learning emerges as an alternative pedagogical approach that emphasizes profound learning processes through awareness, meaningfulness, and joyful experiences. This study aims to examine the optimization of meaningful learning through the application of deep learning within the implementation of the Kurikulum Merdeka in elementary schools. Using a descriptive qualitative method based on literature studies, the findings show that deep learning enhances learning quality through inquiry, projects, problem-solving, collaboration, and the use of technology. However, its implementation is still constrained by limited facilities, digital access gaps, and uneven teacher competencies. The findings highlight the importance of strengthening teacher capacity, providing adequate facilities, and ensuring flexible and contextual learning planning.